(3GdVjGA GddGeY aj TQM LeY GdLhGeYs - (3Mdhdh(B: (3CHh GdYHGS CMeO Hf YHO GdQMef Hf ehSi GdRdjWfj GdbjQhGfj (B((3J (B898(3g`(B)s; (3GdHhQjfj , GdMSf Hf eMeO Hf eMeO Hf MSf GdUahQj GdHhQjfj, HOQ GdOjf,J (B1024 (3g` s
(3ChdgG (B:s
(3hGdfHi bjd gh ef ChUi Gddg Edjg s
(3BNQgG (B:s
(3heG GSQQfG heG CYdefG heG Hg GYde Hg efG s
(3hHgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B219 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B291s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B596s
Keywords: (3CUhd Gdabgs